The effect of alternative assessments in natural science on attitudes towards science in grade 8 girls in South Africa - Wallace, Nicole N (School of Education, 2015)
Attitudes towards science and school science have long been studied because of a desire to keep students in science-related subjects and science-related careers. In South Africa, little research has been done to identify what interventions would encourage students, especially girls, to continue in the sciences. This study focused on the implementation of an alternative assessment in Natural Science in Grade 8 at an all-girls independent school. Students were given an open-ended questionnaire at the beginning and end of the school year to determine their choices for their favourite and hardest parts of Natural Science. These choices acted as a proxy of their attitude towards science. They also completed three sections of the Relevance of Science Education (ROSE) questionnaire in June after the alternative assessment was completed. From this data, three conclusions were made. First, the students had a positive attitude toward the alternative assessment. Second, the students had a positive attitude toward science and showed evidence of the impact of alternative assessments on this attitude. Third, the alternative assessment did not show long term effects on the students' attitude toward science.